THE INFLUENCE OF LIFESTYLE AND CONSUMPTIVE BEHAVIOR ON GENERATION Z FINANCIAL MANAGEMENT (CASE STUDY OF STUDENTS OF FACULTY OF ECONOMICS AND BUSINESS, BANDAR LAMPUNG UNIVERSITY) - Anggra Martha Yudha; Habiburrahman (ZILLZELL MEDIA PRIMA, 2024)
The consumptive lifestyles and behaviors that increasingly dominate today's society can have a significant impact on the ability of generation Z to manage their finances. The purpose of this study is to determine the relationship between the lifestyle of generation Z and their purchasing behavior in financial management, especially in the FEB Bandar Lampung University student environment. The sampling methodology uses the Slovin formula, with a sample of 74 students as respondents. This study used multiple linear regression analysis methods, with the help of the IBM SPSS Statistics 25 program, to process the data. Based on the results of the study, it is known that: (1) Lifestyle variables provide positive and significant results on Financial Management variables, it is explained that T counts > T table (2.043 > 1.994). (2) The variable of Consumptive Behavior gives positive and significant results on the variable of Financial Management it is explained that T counts > T table (4,140 > 1,994). (3) The results of simultaneous tests of lifestyle variables and consumptive behavior have a major effect on financial management, with F values calculated > F tables (79,420 > 3,126). Advice for FEB Bandar Lampung University students is that with a lifestyle that is not excessive or does not waste money on spree and consumptive behavior that is not affected by social media and peer pressure to buy goods that are not for needs but wants, students can improve their finances and manage finances to be more effective and more stable.